The Role of Efficiency Management for Optimizing Corporate Sustainability Performance - Estu Widarwati; Nunik Nurmalasari; Ivan Yusriful Fajar; Nabilla Nur Rohmah (Jurnal Pasar Modal dan Bisnis, 2022)
The improvization of sustainability performance for creating the long-term value requires good governance in order to achieve a high productivity and control costs. Firm’s ability managing assets efficiently should be synergized with good corporate sustainability information disclosure. Efficiency management is important for corporate sustainability. A better firm’s managerial improvement will increase firm’s sustainability performance. This is early study analyzing the firm efficiency for achieving corporate sustainability performance in terms of economic, environmental, or social aspects. Furthermore, the study test the impact of efficiency management on corporate sustainability performance in Indonesian’s non financial industry. This study uses purposive sampling technique and the samples include infrastructure, healthy, industrial, basic material, and non primer sector of IDX in 2019-2020. The analytical tools using descriptive statistic, simple regression, and T-test The results show that efficiency management has a significant effect on corporate sustainability performance. Separated effect of efficiency management significant on economic aspect but different finding on environment and social aspect. Next research should explore deeply the topic using long period and complex model approac. The finding this study lead to the significance of efficiency management as breakthrough for optimizing corporate sustainability performance.